2017
DOI: 10.5765/jkacap.2017.28.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Body Weight Perception, and Depressed Mood in Korean Adolescents

Abstract: Objectives:We examined the relationships between the body mass index, body weight perception, and depressed mood in a nationally representative sample of Korean adolescents. Methods: We analyzed the data from the 2013 Korean Youth Risk Behavior Web-based Survey and evaluated the relationships between the body mass index, body weight perception, and depressed mood by gender (36655 boys and 35780 girls). Results: For boys, a low body mass index and perceiving oneself as underweight were related to depressed mood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In a nationwide survey on the health behaviors of Korean adolescents (12–18 years), a similar finding has been reported, but only in boys [10]. It may be because boys expected to have a muscular body and any deviation from this ideal led them to feelings of depression [28,30]. One possible explanation for differences between the findings of the current study in Iran and the Korean survey is that the perception of being underweight, despite actually being a normal weight, may be an expression of body dissatisfaction that would lead to lack of self-confidence as well as feelings of depression.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In a nationwide survey on the health behaviors of Korean adolescents (12–18 years), a similar finding has been reported, but only in boys [10]. It may be because boys expected to have a muscular body and any deviation from this ideal led them to feelings of depression [28,30]. One possible explanation for differences between the findings of the current study in Iran and the Korean survey is that the perception of being underweight, despite actually being a normal weight, may be an expression of body dissatisfaction that would lead to lack of self-confidence as well as feelings of depression.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, a study on Chinese adolescents reported that perceived weight status (overweight or underweight) not actual weight status, was associated with psychological disorder in both genders [9]. The Korean Youth Risk Behavior Web-based Survey showed that girls who perceived themselves as underweight or overweight, as well as boys who perceived themselves as underweight, were at a higher risk of depression [30]. Self-perception of weight depends on subjective appraisement of reality, although it may not always reflect reality, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that evaluated the relationships between the body mass index (BMIs), body weight perception and depressed mood among Korean adolescents found that a low BMI and perceiving oneself as underweight were related to a depressed mood among adolescent boys. However, for girls, both low and high BMI were negatively related to depressed mood (Lim & Kim, 2017 States, and Australia. This study was conducted in a major urban city of a low-and middle-income country, namely, Mumbai in India, to determine the prevalence of depression among 10-to 17-year-old adolescents and to assess sleep patterns, eating habits and body weight status.…”
Section: Key Messagesmentioning
confidence: 93%
“…Another study that evaluated the relationships between the body mass index (BMIs), body weight perception and depressed mood among Korean adolescents found that a low BMI and perceiving oneself as underweight were related to a depressed mood among adolescent boys. However, for girls, both low and high BMI were negatively related to depressed mood (Lim & Kim, 2017). The findings from these studies highlight the significance of body weight status as a determinant of depression symptoms and that adolescents who are not at their normal weight, both underweight and overweight, may be at an increased risk for depression.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies about body image and health have been conducted with adolescents [15][16][17][18] with the assumption that the perception of body image is affected by pubertal development. However, the physical changes that occur in adulthood also have the potential to affect body image, since, in this stage, body shape can move away from the aesthetics of sociocultural ideals of physical beauty 19 .…”
Section: Resultsmentioning
confidence: 99%